Intercultural Communication in Miracle in Cell No. 7 Movie : Comparative Study Between Korea and Indonesia Version - Syamsul Bahri; Lateresiana Kemit; Ezra Agnes Sibarani; Naurah Syifa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Film serves as a vital medium for reflecting cultural values and functions as an effective tool for intercultural communication. This study explores the differences in communication styles between the Korean and Indonesian adaptations of Miracle in Cell No. 7, focusing on how culture influences the expression of emotions, authority, and moral values through verbal and nonverbal elements. Employing a mixed-method approach, this research integrates qualitative thematic analysis (Braun & Clarke, 2006) to examine key scenes, along with quantitative coding to statistically compare communicative elements. Hall’s (1976) theory of high-context and low-context communication provides the main theoretical framework to understand the intercultural distinctions between the two versions. The results show that the Korean adaptation relies more heavily on gestures (53.33%), such as physical aggression and exaggerated movements, while the Indonesian version (42.86%) places greater emphasis on verbal articulation and religious expression. Dramatic tonal shifts are more common in the Korean version (26.67%), whereas the Indonesian adaptation (28.57%) maintains a more controlled tone of voice. Facial expressions are more exaggerated in the Korean version (6.67%), particularly in scenes involving authority, while the Indonesian characters (9.52%) display subtler and more restrained expressions. Implicit communication, including religious symbolism, is more prominent in the Indonesian adaptation (19.05%), incorporating Islamic prayers and teachings, whereas the Korean version (13.33%) subtly includes Christian elements. This study reveals that while both adaptations reflect high-context communication cultures, the Korean version emphasizes physical expressiveness and hierarchical interaction, while the Indonesian version highlights verbal communication, religious themes, and emotional restraint. These findings reinforce the role of cinema as a medium for identity representation and cross-cultural understanding.